Age‐related factors that affect B cell responses to vaccination in mice and humans. Issue 1 (2nd June 2020) - Frasca, Daniela; Blomberg, Bonnie B.; Garcia, Denisse; Keilich, Spencer R.; Haynes, Laura
Abstract: Aging significantly changes the ability to respond to vaccinations and infections. In this review, we summarize published results on age‐related changes in response to infection with the influenza virus and on the factors known to increase influenza risk infection leading to organ failure and death. We also summarize how aging affects the response to the influenza vaccine with a special focus on B cells, which have been shown to be less responsive in the elderly. We show the cellular and molecular mechanisms contributing to the dysfunctional immune response of the elderly to the vaccine against influenza. These include a defective interaction of helper T cells (CD4+) with B cells in germinal centers, changes in the microenvironment, and the generation of immune cells with a senescence‐associated phenotype. Finally, we discuss the effects of aging on metabolic pathways and we show how metabolic complications associated with aging lead to immune dysfunction.